(untitled) (Chemical Engineering Research Bulletin, 2023)
Due to their detrimental impact on air quality and climate change, fugitive emissions originating from the unintentional escape of gases and vapors from industrial processes have generated concerns. The present study investigates the effects of fugitive emissions from petroleum processing facilities on the workplace and global warming. A bitumen plant and a condensate refinery were selected for case studies. Process flow diagrams and piping and instrumentation diagrams were used to estimate the fugitive emissions from different units of the plants with the help of emission factors. The emissions from the refinery were four times higher than those from the bitumen plant. The cancer risks of the plant employees exposed to fugitive emissions were assessed considering worst-case scenarios. Workers in both plants were found to be susceptible to cancer risk to a certain degree. Additionally, the contribution of fugitive emissions to global warming was estimated using yearly equivalent carbon dioxide (CO2) emissions. The present study demonstrates ways to approximate fugitive emissions and their impacts at the design stage facilitating corrective measures with minimum cost implications. Chemical Engineering Research Bulletin 23(2023): 46-51